2019
DOI: 10.1002/solr.201900104
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of In‐Plane Charge Transport in Hole Transfer Layer to Achieve High Fill Factor for Inverted Planar Perovskite Solar Cells

Abstract: Charge extraction at the active layer‐electrode interfaces is critical in obtaining highly efficient planar perovskite solar cells (PSCs). It is commonly achieved by enhancing the charge carrier mobility of the charge transfer layer (CTL) that possesses a desirable energy level. Nevertheless, the in‐plane movement of charge carriers in the CTL possibly leads to severe charge recombination in the presence of defects at the interfaces. To verify this overlooked possibility, herein, an oxidized monolayer of poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…Therefore, the corresponding energy level schematic of the p-i-n planar PSCs is shown in Figure 1h. [29,31] The well-matched energy level between HTL and perovskite layer will reduce the carrier recombination at the interface and simultaneously suppress the energy loss of hole transport, [47,48] contributing to higher V OC and outstanding PSCs performance. [34,49] Then the surface properties of different HTLs are evaluated by measuring the contact angles of dimethyl sulfoxide (DMSO) droplets on PEDOT:PSS, SBS-3-PEDOT:PSS, SBS-9-PEDOT: PSS, and SBS-15-PEDOT:PSS films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the corresponding energy level schematic of the p-i-n planar PSCs is shown in Figure 1h. [29,31] The well-matched energy level between HTL and perovskite layer will reduce the carrier recombination at the interface and simultaneously suppress the energy loss of hole transport, [47,48] contributing to higher V OC and outstanding PSCs performance. [34,49] Then the surface properties of different HTLs are evaluated by measuring the contact angles of dimethyl sulfoxide (DMSO) droplets on PEDOT:PSS, SBS-3-PEDOT:PSS, SBS-9-PEDOT: PSS, and SBS-15-PEDOT:PSS films.…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28] Therefore, the modification of the HTL/perovskite interface plays an important role in achieving efficient charge transfer, reducing recombination, and controlling the morphology of the perovskite film. [29][30][31] To solve the acidic issue, Elbohy et al reported a strategy to tune the acidic nature of PEDOT: PSS by adding urea, where the PCE was increased from 14.4% to 18.8%. [32] Wang et al applied a mild base of imidazole to tune the pH value of the PEDOT:PSS, which can neutralize the acidity and thus largely improve the long-term stability of PSCs.…”
mentioning
confidence: 99%
“…[200] Recently, Sun et al found that the inhibition of the in-plane charge transport in PEDOT:PSS decreased the carrier recombination and yielded a highest PCE of 18.8% with a FF of 0.82 for PerSCs. [251] It is found that H 2 O 2 oxidized PEDOT:PSS monolayer shows a comparable charge transfer ability in the out-of-plane direction, but a higher in-plane resistance compared with the pristine PEDOT:PSS monolayer mainly due to the decreased conjugation length (Figure 15c,d). Such improved balance of charge transport in both in-plane and out-of-plane directions is responsible for lower surface carrier recombination and higher PCE.…”
Section: Modification Of Pedot Htlmentioning
confidence: 92%
“…[250] Till now, PEDOT:PSS-based planar PerSCs yielded a highest PCE of 18.8%. [251] Researches on PEDOT:PSS HTL in QDSCs is still in its infancy. Wang et al reported the use of PEDOT:PSS in p-i-n PbS-based QDSCs enabled more efficient charge collection and extraction than that of NiOx-and V 2 O 5 -based devices, leading to increased PCE.…”
Section: Progress Of Pedot Htl For Oscs Perscs and Qdscsmentioning
confidence: 99%
See 1 more Smart Citation